Influence of Fabrication Conditions on the Magnetic Properties of MnFe2O4 Nanoparticles Synthesized by Hydrothermal Method - Duy Xuan, Nguyen; Trung Hieu, Dao Xuan; Duy Cuong, Le; Thi Anh, Ho (VNU Journal of Science: Mathematics - Physics, 2025)
Manganese ferrite (MnFe 2 O 4 ) nanoparticles have attracted significant research interest due to their unique magnetic properties and diverse applications in high-frequency devices, biomedical systems, and environmental treatment. In this work, we systematically investigated the influence of reaction times (T r = 1–5 h) and pH values (4–13) on the crystallinity, morphology, and magnetic properties of MnFe 2 O 4 nanoparticles synthesized by hydrothermal method at 150 °C. The samples characterization was carried-out by XRD, Fe-SEM, and VSM measurements. The experimental results demonstrated that optimal conditions were achieved at a pH value of 11 with T r = 4 h, producing like-spherical nanoparticles with an average size of 25 nm. However, due to some agglomeration, the overall particle size distribution ranged from 15 to 60 nm, with an average size in non-aggregated regions around 40 nm. These nanoparticles exhibited outstanding magnetic properties, including a high saturation magnetization of ~ 57 emu/g, a low coercivity of ~ 22 Oe, and an experimental magnetic moment value of about 2.35 μ B . In contrast, lower pH values or varying reaction times led to impurities and reduced magnetic performance. Additionally, the effects of annealing temperatures (200 – 800 °C) on the magnetic properties were explored. These results provide crucial insights into the synthesis-structure-property relationships in MnFe₂O₄ nanoparticles and establish practical guidelines for producing high-quality MnFe 2 O 4 nanoparticles for applications in various fields.